A method for producing a soil nutrient map with reduced number of soil sample - Mohamed Shariff, Abdul Rashid; Zolfagharnassab, Shahrzad; Bejo, Siti Khairunniza (2012)
The present invention relates to a method for producing a soil nutrient map using reduced number of soil sample required to be taken in a geographical region, characterized by the steps of: obtaining a first database comprising data of a plurality of soil samples taken from the geographical region; supplying the first database to an artificial neural network for training, validating and testing said artificial neural network; providing an input of the plurality of soil samples to the trained artificial neural network, wherein said trained artificial neural network evaluates the input and outputs a second database of virtual soil samples representing non-sampled area of the geographical region; and forming the soil nutrient map from the first database and the second database.